Development and evaluation of a fibre optic web-based learning module for technology-based learners - Ong, Sylvia Al Ling (2003)
Web-based learning module provide integrated environments of various technologies to support and enhance learners learning process via the Internet. Therefore it was the interest of the researcher to develop a 'Fibre Optics Web-Based Learning' (FOWBL) module and evaluate its effectiveness. An instructional design model, ADDLE was followed throughout the development of the web-based learning module. Furthermore, design factors such as multimedia, which facilitate the web-based learning program were discussed. This paper reported the result from the research, which study the effectiveness of web-based learning module for technology-based learners. A sample of 24 respondents, which comprised of 12 Telekom Malaysia learners and 12 Kolej Latihan Telekom staff were selected. The findings were discussed based on the best design factors via-online web learning program, user-friendliness, satisfaction in learning strategies, content satisfaction, learners' ability of understanding the content, motivation, skill and knowledge enhancement and to investigate whether there is any significant differences in the learners' understanding among the beginner, intermediate and advanced learners. The learners' satisfaction towards the developed FOWBL module was highly rated through the overall mean scores obtained for this research and there was a significant difference between the learners' online quiz performance with their knowledge levels when accessing the learning program. This research was a survey research. The researcher implemented both qualitative and quantitative research. Therefore the questionnaires created utilized the Likert scale for valid statistical analysis. Furthermore, interview and online quiz were developed to support the research findings. The data collected pinpoint the weaknesses and strengths of the developed FOWBL program. The research closed with recommendations for the development and use of web-based learning tools that take into account the importance of usability issues in the choice of web-based learning tools and recognition of the situation of learners and educators within real life contexts.